Air microbial sampling in operating theatres by active and passive methods: equation correlation from the GISIO-ISChIA study results and comparison with the EU GGMP recommendation, towards the definition of threshold values : Air microbial sampling in operating theatres: comparison between active and passive methods - Pasquarella, Cesira Isabella Maria; Auxilia, Francesco; Barchitta, Martina; Cristina, Maria Luisa; D'Alessandro, Daniela; Mura, Ida; Nobile, Marta; Veronesi, Licia; Albertini, Roberto; Agodi, Antonella (Acta Biomedica Atenei Parmensis, 2023)
The aim of this study was to calculate the equation of correlation between the microbial air contamination values obtained by active sampling (colony-forming units per cubic metre, CFU/m3) and by passive sampling (Index of microbial air contamination, IMA), by using the data from the ISChIA study, and to compare the values obtained with the recommended limits defined by the EU Guidelines to Good Manufacturing Practice (EU GGMP), 2008, for clean areas used to manufacture sterile medicinal products. Air sampling was performed during 335 elective prosthesis procedures. Correlation between CFU/m3 and IMA values was evaluated using the Spearman test; p<0.05 was considered to indicate significance. This equation was used to calculate the IMA values corresponding to the CFU/m3 recommended threshold values by EU GGMP for the different Grades of microbial contamination. The following correlation equation was obtained: y = 1.86 + 0.12x, where “x” = cfu/m3 value and “y” = IMA value. The relationships between CFU/m3 and IMA values obtained from active and passive sampling during the ISChIA study showed to be in line to those suggested by the EU GGMP for pharmaceutical manufacturing for Grade C and D. This study shows that the EU GGMP relationship could be considered valid also for operating theatres. Both methods, active and passive samplings, can be used to evaluate microbial air quality and highlight critical situations; however, in particular during the activity, passive sampling estimating the risk posed by airborne microorganisms to the surgical wound, can be considered more relevant, and for its simplicity, economy and standardization, can be suggested for routine microbial monitoring.